The molecular phylogenetic signature of Bali cattle revealed by maternal and paternal markers - S. M. F., Syed-Shabthar; M. K. A., Rosli; N. A. A., Mohd-Zin; S. M. N., Romaino; Z. A., Fazly-Ann; M. C., Mahani; O., Mazni; R., Zainuddin; S., Yaakop; B. M., Md-Zain (Springer Netherlands, 2013)
Bali cattle is a domestic cattle breed that can be found in Malaysia. It is a domestic cattle that was purely derived from a domestication event in Banteng (Bos javanicus) around 3,500 BC in Indonesia. This research was conducted to portray the phylogenetic relationships of the Bali cattle with other cattle species in Malaysia based on maternal and paternal lineage. We analyzed the cytochrome c oxidase I (COI) mitochondrial gene and SRY of Y chromosome obtained from five species of the Bos genus (B. javanicus, Bos gaurus, Bos indicus, Bos taurus, and Bos grunniens). The water buffalo (Bubalus bubalis) was used as an outgroup. The phylogenetic relationships were observed by employing several algorithms: Neighbor-Joining (PAUP version 4.0), Maximum parsimony (PAUP version 4.0) and Bayesian inference (MrBayes 3.1). Results from the maternal data showed that the Bali cattle formed a monophyletic clade, and together with the B. gaurus clade formed a wild cattle clade. Results were supported by high bootstrap and posterior probability values together with genetic distance data. For the paternal lineage, the sequence variation is low (with parsimony informative characters: 2/660) resulting an unresolved Neighbor-Joining tree. However, Bali cattle and other domestic cattle appear in two monophyletic clades distinct from yak, gaur and selembu. This study expresses the potential of the COI gene in portraying the phylogenetic relationships between several Bos species which is important for conservation efforts especially in decision making since cattle is highly bred and hybrid breeds are often formed. Genetic conservation for this high quality beef cattle breed is important by maintaining its genetic characters to prevent extinction or even decreased the genetic quality.